Identification and Explanation of the Requirements of ‎‎E-teaching/learning, Proportionate to Characteristics of Today's BA Level Students - ahmad ebrahimi; Sayed Ebrahim Mir Shah Jafari; ali rabbani (Shahid Chamran University of Ahvaz, 2021)
Introduction:Newfound technologies in the communication and information area lead the educational systems ‎‎toward electronic teaching-learning.‎ certainly, the application of e-learning strategy based on ‎components tailored to the needs, desires and skills of students, leads to the creation of numerous ‎and diverse learning opportunities for students. In contrast, the inappropriateness and adaptation ‎of academic activities to the characteristics of students is a cause of motivation and ‎academic failure. The present study tries to identify and explain the requirements of e-‎teaching/learning which are fit for the characteristics of today's BA students. ‎Method:The research design is mixed and of successive exploratory type. The qualitative part was done using the case study method and the quantitative part was done using the descriptive-survey method. The tools of the qualitative section are semi-structured interviews and the tools of the quantitative section are researcher-made questionnaires. The statistical population of the qualitative section was experts in the two fields of educational sciences and social sciences, of which the sample of them continued purposefully until the saturation of information. The statistical population in the quantitative section consisted of faculty members and BA ‎students of educational and social sciences colleges of Tehran and Isfahan Universities of which the sample of them was chosen with the stratified ‎random method according to the volume. The analysis of the findings in the qualitative part is based on grounded theory and in the quantitative part is based on descriptive and inferential statistics.Results:Regarding the research findings, the most important Requirements of electronic teaching-learning ‎strategy which suits the characteristics of today's BA students is: using virtual messengers, using ‎soft wares and educational videos, using scientific websites, using remote supplementary trainings, ‎being allowed to search the Internet in classroom, having virtual assignments, taking virtual ‎exams and using smart board.‎Discussion:Based on the findings, it can be concluded, the application of these elements, ‎‏leads to academic ‎motivation and scientific ‎growth of today's students‏ ‏and thus, it is recommended to Professors for ‎the purpose of ‎effective teaching and optimal use of educational opportunities, do not neglect to ‎use them.‎ Universities must also provide the necessary equipment for e-teaching, especially smart ‎boards and high-speed Internet. In addition, in order to acquaint professors and students with e-‎learning skills such as the use of scientific websites, distance education, the use of smart boards, ‎virtual exams, etc., organized training workshops and encourage professors who use these ‎methods.